Beyond Family: Modeling Non-hereditary Heart Diseases With Human Pluripotent Stem Cell-Derived Cardiomyocytes - Martewicz, Sebastian; Magnussen, Michael; Elvassore, Nicola (Frontiers in Physiology, 2020)
Non-genetic cardiac pathologies develop as an aftermath of extracellular stress-conditions. Nevertheless, the response to pathological stimuli depends deeply on intracellular factors such as physiological state and complex genetic backgrounds. Without a thorough characterization of their in vitro phenotype, modeling of maladaptive hypertrophy, ischemia and reperfusion injury or diabetes in human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) has been more challenging than hereditary diseases with defined molecular causes. In the past several years, better insights into hPSC-CM in vitro physiology and advancements in technological solutions and culture protocols generated cell types displaying stress-responsive phenotypes reminiscing in vivo pathological events and unlocking their application as a reductionist model of human cardiomyocytes, if not yet of the adult human myocardium. Here, we provide an overview of the available literature of pathology models for cardiac non-genetic conditions employing healthy (or asymptomatic) hPSC-CMs. In terms of numbers of published articles, these models are significantly lagging behind monogenic diseases, which misrepresents the incidence of heart disease causes in the human population.